Keanekaragaman Jenis dan Kepadatan Ikan di Padang Lamun Pantai Desa Akoon Kecamatan Nusalaut Kabupaten Maluku Tengah - Tahapary, Rian; Tuaputty, Hasan; Liline, Sintje; Kurnia, Tri Santi; Kubangun, Muhammad Tarmizi (bionature, 2019)
Abstract. One of the ecological roles of seagrass beds is as fish habitat and the presence of seagrasses can affect the diversity and density of fish in a water. Distribution of seagrass vegetation in the waters of the village of Akoon is quite extensive with conditions that are also quite diverse, allowing the many types of fish that live in the seagrass beds in the village of Akoon. Nusalaut, Central Maluku Regency. The results of the study describe the types of fish that are in the seagrass beds in the village of Akoon are 17 species with 80 individuals. Fish species diversity index in the seagrass beds in Akoon village, Nusalaut sub-district was 2,434, evenness index was 0.859, and wealth index was 1,900. Fish in seagrass beds in Akoon village, Nusalaut sub-district have a density value of 0.2 ind / m2. Keywords: diversity, density, seagrass fish, Akoon Village